Programa de excursiones educativas en directivos y docentes para mejorar la gestión del clima institucional de la I. E. Maynas 2024 - Acosta Vilchez, Sandra Gissela (2025)
The primary objective of this study was to evaluate the effect of the educational excursions program on the improvement of institutional climate management among leaders and teachers at the Maynas Educational Institution in 2024. The study employed a longitudinal, univariate, field, and quasi-experimental design, involving an experimental group and a control group, composed of 45 leaders and teachers who formed the sample. This research was classified as evaluative. A written case performance test was administered both as a pre test and post-test. This data collection instrument was evaluated by experts prior to its implementation. Statistical analysis revealed that, following the intervention of the educational excursions program, the means of institutional climate management and its dimensions—job satisfaction, perceived quality of education, leadership, and collaboration—were significantly higher in the experimental group compared to the control group. The experimental group’s scores ranged between 14.20 and 14.27, whereas the control group’s scores ranged between 9.93 and 10.69. The non-parametric test and a p-value less than 0.05 confirmed that these differences are highly significant, leading to rejection of the null hypothesis and acceptance that the program had a positive impact on institutional climate management. These findings demonstrate the program’s effectiveness and support the overall hypothesis of the study.